The impact of race on postpartum opioid prescribing practices: a retrospective cohort study - Tyler R. McKinnish; Adam K. Lewkowitz; Ebony B. Carter; Ashley E. Veade (BMC, 2021)
Abstract Background To identify the association between inpatient postpartum opioid consumption, race, and amount of opioids prescribed at discharge after vaginal or cesarean delivery. Methods A total of 416 women who were prescribed an oral opioid following vaginal or cesarean delivery at a single tertiary academic institution between July 2018 and October 2018 were identified. Women with postoperative wound complications, third and fourth degree lacerations, cesarean hysterectomy, or a history of opioid abuse were excluded. The primary outcome was the number of oxycodone 5 mg tablets prescribed at discharge, stratified by race and mode of delivery. Only "Black" and "White" women were included in analyses due to low absolute numbers of other identities. Black women were compared to white women using multivariable logistic regression. Multiple sensitivity analyses were performed. Results The median number of oxycodone tablets consumed during hospitalization following cesarean delivery was seven (IQR: 2.5-12 tablets) and following vaginal delivery was one (IQR: 0-3). White women were more likely to be older at delivery regardless of route (median 32 vs. 30 years for cesarean delivery, and 29 vs. 27 years for vaginal delivery; p < 0.01 for both). White women undergoing cesarean delivery did so at a lower maternal BMI (31.6 vs. 34.5; p = 0.02). White women were also significantly more likely to have private insurance and to experience perineal lacerations following vaginal delivery. The number of inpatient opioid tablets consumed, as well as the number prescribed at discharge, were not statistically different between Black and White women, regardless of mode of delivery. These findings persisted in sensitivity analyses. Conclusion At our large, academic hospital the number of tablets prescribed at discharge had no association with patient race or inpatient usage regardless of mode of delivery.